Pengaruh Format Iklan Komparatif dan Non Komparatif Terhadap Respon Kognitif dan Niat Perilaku - Bikorin, Bikorin; Fatmawati, Indah (Universitas Muhammadiyah Yogyakarta, 2016)
This research aimed to analyze the influence of comparative advertisement format and non comparative toward cognitive responses and behavioral intentions. In this research, the writer chooses the participants who used mobile cards XL Axiata (XL and Axis) in Special Region of Yogyakarta area. In analyzing the data, the writer uses the quantitative and experiment method conducted by survey. In this research, the writer uses questionnaire for collecting the data. The samples of this research are card mobile users of XL Axiata (XT and Axis) who live in Special Region of Yogyakarta area and fulfill criteria set by the researcher. The number of the samples in this research is 80 participants. The analysis tool in this research, the writer uses the analysis of independent sample t test, two ways anova dan simple regression.Some of the research findings are; there are difference influences between cognitive response of consumers who receive comparative advertising stimuli and noncomparative ads. Then there are average differences between the cognitive responses by stimuli comparative advertising/non-comparative and NFC low/high. The last, a cognitive response effects on consumer behavioral intentions.